Bronchodilator response and lung function decline: Associations with exhaled nitric oxide with regard to sex and smoking status - Elisabet Nerpin; Diogenes Seraphim Ferreira; Joost Weyler; Vivi Schlunnsen; Rain Jogi; Chantal Raherison Semjen; Thorainn Gislasson; Pascal Demoly; Joachim Heinrich; Dennis Nowak; Angelo Corsico; Simone Accordini; et al. (World Allergy Organization Journal, 2021)
Background: Fractional exhaled nitric oxide (FeNO) is a marker of type-2 inflammation used both to support diagnosis of asthma and follow up asthma patients. The associations of FeNO with lung function decline and bronchodilator (BD) response have been studied only scarcely in large populations. Objectives: To study the association between FeNO and a) retrospective lung function decline over 20 years, and b) lung function response to BD among asthmatic subjects compared with non-asthmatic subjects and with regards to current smoking and sex. Methods: Longitudinal analyses of previous lung function decline and FeNO level at follow-up and cross-sectional analyses of BD response and FeNO levels in 4257 participants (651 asthmatics) from the European Community Respiratory Health Survey. Results: Among asthmatic subjects, higher percentage declines of FEV1 and FEV1/FVC were associated with higher FeNO levels (p = 0.001 for both) at follow-up. These correlations were found mainly among non-smoking individuals (p = 0.001) and females (p = 0.001) in stratified analyses.Percentage increase in FEV1 after BD was positively associated with FeNO levels in non-asthmatic subjects. Further, after stratified for sex and smoking separately, a positive association was seen between FEV1 and FeNO levels in non-smokers and women, regardless of asthma status. Conclusions: We found a relationship between elevated FeNO and larger FEV1 decline over 20 years among subjects with asthma who were non-smokers or women. The association between elevated FeNO levels and larger BD response was found in both non-asthmatic and asthmatic subjects, mainly in women and non-smoking subjects.